Penta Helix Collaboration Model in Handling Problems of Waste Management - Diana Hertati; Nurhadi; Tukiman (Nusantara Science and Technology Proceedings, 2022)
Population growth and socio-economic activities in the area are positively correlated with an increase in the amount and type of waste and pose a threat to regional ecosystems. The condition of the Ngimpik Final Disposal Site (TPA) is over capacity. The role of the community is needed to change the perspective on the waste that was previously collected, transported, and disposed of to reduce, separate, and utilize waste. Therefore, it is necessary to have a penta helix collaboration between stakeholders in waste management which is possible to overcome the problems of waste management. The research location is the Office of the Environmental and Hygiene Office of Gersik Regency. The research method uses a qualitative approach and data sources are obtained from secondary data, literature studies, interviews, and field visits. Informants were taken from formal figures, the Head of the Department of Cleanliness and the Environment and their staff, the community, and the private sector. Methods of data collection are done using interviews, focused groups, and discussions. This research is expected to result in the application of the concept of a penta helix collaboration model in dealing with waste management problems with a focus on describing the role of the Penta Helix collaboration in the TPST program. A solution to handle the problem of waste management in Gresik Regency through the concept of the Penta Helix collaboration. Data analysis was carried out using qualitative analysis by Miles and Huberman (2014) consisting of four components, namely: data collection (data collection), data condensation (data condensation), data presentation (data display), and drawing conclusions or verification (conclusion and verifying drawings). The results of the study indicate that the community's perspective on waste management has not been effective in terms of collecting, transporting, and disposing of waste to reduce, separate, and utilize waste. The SAMTAKU program has challenges due to internal inhibiting factors (awareness, motivation, and participation) and external inhibiting factors (commitment, trust, communication, and coordination). The Penta Helix collaboration is a solution to handling waste management by dividing the roles of academics as drafters, businessmen as enablers, communities as accelerators, government (government) as regulators, and media as expanders. Keywords: Penta Helix Collaboration, Waste Management, Samtaku Program.